2011
DOI: 10.1063/1.3553366
|View full text |Cite
|
Sign up to set email alerts
|

The Beryllium tetramer: Profiling an elusive molecule

Abstract: The structure and energetics of Be(4) are investigated using state-of-the-art coupled-cluster methods. We compute the optimized bond length, dissociation energy, and anharmonic vibrational frequencies. A composite approach is employed, starting from coupled-cluster theory with single, double, and perturbative triple excitations extrapolated to the complete basis set (CBS) limit using Dunning's correlation consistent cc-pCVQZ and cc-pCV5Z basis sets. A correction for full triple and connected quadruple excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 116 publications
6
32
0
Order By: Relevance
“…This feature of the PEC has also been confirmed recently at the most rigorous levels of theory 100104. For $X^1\Sigma^+ {\rm Be}_2$ , calculations that do not incorporate the effects of triple and quadruple excitations from the RHF wave function generally fail to locate the minimum on the PES 99, 100, 103. Schmidt et al102 also compared a number of ground state energy surfaces of the Be‐dimer generated via the current generation high‐level SRCC methods using a revised version of the aug‐cc‐pVQZ set (containing 5s,4p,3d,2f,1g contracted functions, which are augmented by a set of s,p,d,f,g functions with small exponents).…”
Section: Ground State Energy Surface Of the Van Der Waals' Molecule $supporting
confidence: 52%
“…This feature of the PEC has also been confirmed recently at the most rigorous levels of theory 100104. For $X^1\Sigma^+ {\rm Be}_2$ , calculations that do not incorporate the effects of triple and quadruple excitations from the RHF wave function generally fail to locate the minimum on the PES 99, 100, 103. Schmidt et al102 also compared a number of ground state energy surfaces of the Be‐dimer generated via the current generation high‐level SRCC methods using a revised version of the aug‐cc‐pVQZ set (containing 5s,4p,3d,2f,1g contracted functions, which are augmented by a set of s,p,d,f,g functions with small exponents).…”
Section: Ground State Energy Surface Of the Van Der Waals' Molecule $supporting
confidence: 52%
“…Our aim is a deeper understanding of interaction forces leading to much higher stability of Be clusters in comparison with the smallest Be 2 species. In the recent paper on Be pentamers and tetramers from Schaefer's group [8,9], authors analysed the IE of these complexes in terms of sequential dissociation energies for Be 2À5 clusters. They found that the magnitude of the energy necessary for the dissociation of the tetramer to Be 3 + Be stands out from the trend.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11,[18][19][20][21][22][23][24][25][26][27] A number of fac-tors complicate the bonding in these molecules, including orbital hybridization, multiconfigurational effects, strong dynamical correlation, and the small 2s-2p energy gap in atomic beryllium. [7] Previous work on these clusters has been reviewed elsewhere; [1,7,9,17,28] we rehearse the highlights here. The dimer and the trimer both have a formal bond order of zero and neither is bound at the Hartree-Fock (HF) level of theory.…”
Section: Introductionmentioning
confidence: 91%
“…Theory predicts significant jumps in the atomization energy for the next two clusters, with D e = 17.2 kcal mol À1 for Be 3 [8] and D e = 89.7 kcal mol À1 for Be 4 . [9] The atomization energy of the Be 5 cluster is thought [10,11] to lie well above 100 kcal mol À1 . Beryllium clusters continue to provoke significant theoretical interest and serve as a proving ground for high-level theoretical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation